New Configurations of Low-Cost Dual-Polarized Printed Antennas for UWB Arrays. (8th March 2012) - Valerio, Guido; Mazzocchi, Simona; Galli, Alessandro; Ciattaglia, Matteo; Zucca, Marco
Abstract : A novel class of structures is proposed to realize ultra-wide-band radiating elements for large arrays, providing dual polarization, beam scanning, and compact and inexpensive realization based on suitable rhombic arrangements of dipoles printed on low-cost layered substrates. In a first implementation, four rhombic shapes, orthogonally placed on the same layer, provide two orthogonal polarizations. In a second implementation, the two polarizations are excited by two rhombic shapes printed on two different layers in a stacked-patch-like arrangement. This latter structure leads to a better lateral shielding of the single radiating element, in order to reduce mutual interactions among adjacent elements in array environment. The behavioral features of these antennas have been tested with various parametric analyses. Practical aspects have been addressed such as the choice of appropriate feeding and of commercially available dielectric layers. The resulting antennas are matched at the input ports in an extremely wide range of frequencies (5–25 GHz), covering various microwave applications, such as aircraft surveillance, weather polarimetric radars, and control and communications systems. Good radiating features, in terms of pattern shape and gain, are observed in a large band of frequencies. The basic scanning performance of large and small array configurations is finally investigated.